Juridik eller socialpedagogik? Skolors strategier för att hantera kränkningar (Sociologisk Forskning, 2016)
Legal perspectives or Social Pedagogy? Schools strategies of handling harassmentsThe present study explores how Swedish schools define and categorize situations when students have been exposed to different forms of abusive acts and violence at school. The empirical study is designed as case studie of two urban secondary schools situated in areas with different socioeconomic conditions. One of the schools is located in a suburb in one of the most economically disadvantaged areas in a greater city area. The other school is located in a small town municipality, where the students are relatively privileged in respect to their socio-economic backgrounds. The results indicate that different socio-economic conditions influence how professional’s describe and categorize violence and harassment and the types of strategies chosen. In the suburban school professionals talk and collaborate with the police, reporting cases of violence and harassment. In the small town school the professionals talk about the importance of collaborating with parents.
Keywords: categorizations; harassment; school; segregation; violence